Comparison between selective head cooling and whole-body cooling in neonatal therapeutic hypothermia - Souza, Guilherme Rangel e; Zambeli, Letícia de Oliveira; Ruela, Vinícius Parma; Silveira, Anna Carolina Bovarêto; Maia, Maria Eduarda Dias; Freitas, Geandra Martins de; Vieira, Julia Machado; Alvim, Vitor Fernandes (ABCS Health Sciences, 2022)
Introduction: Experimental evidence, as well as improved clinical studies of the reduction of brain injury and, improves the neurological outcome, in newborns with hypoxic-ischemic encephalopathy (HIE) occurring in therapeutic hypothermia (TH). Objective: To verify the potential of hypothermic hypoxic-ischemic encephalopathy (HIE) therapy in neonatal asphyxia, based on literature data, comparing the benefits between selective head cooling (SHC) and whole-body cooling (WBC), see that the use of TH as a standard treatment in newborns with moderate or severe HIE has been adopted. Methods: A search was performed in the PubMed and SciELO databases of human studies, using the keywords “Therapeutic Hypothermia”, “Induced Hypothermia”, and “Hypoxic-Ischemic Encephalopathy”, “Selective cooling of the head”, “Total body cooling” and its variables. Results: Eleven articles were selected to compose the review, after detailed reading. There is a consensus, that the reduction of the risk of death or disability at 18 months of life in neonates with moderate to severe HIE, occurs to TH through the techniques of WBC or SHC. It was found in the studies that there is no difference in terms of adverse effects between the two methods. As for radiological changes, such as hypoxic-ischemic injuries and the incidence of seizures after cooling, they are more frequent with SHC. Conclusion: Both WBC and SHC demonstrated neuroprotective properties, although WBC provides a broader area of brain protection. However, no significant differences were found between the methods in terms of adverse effects and beneficial short or long-term results.